2013
DOI: 10.2298/abs1302455k
|View full text |Cite
|
Sign up to set email alerts
|

Gender modulates development of the metabolic syndrome phenotype in fructose-fed rats

Abstract: We analyzed the effects of a fructose-rich diet (FRD) to test the assumption that the expression of metabolic syndrome phenotype is different in male and female rats. Two-way ANOVA revealed a significant effect of FRD on feeding behavior and carbohydrate/lipid metabolism. The increased caloric intake in FRD rats of both sexes was followed by a cluster of gender-specific changes typical for the metabolic syndrome. Female rats were characterized by decreased glycemia, increased triglycerides, enlarged visc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 26 publications
3
14
1
Order By: Relevance
“…Systemic insulin resistance was not observed in this animal model, as we previously confirmed by unaltered HOMA index and intraperitoneal glucose tolerance test [63]. Interestingly, plasma glucose was not increased, but even decreased, pointing to elevated insulin sensitivity, although the plasma insulin was unaltered.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Systemic insulin resistance was not observed in this animal model, as we previously confirmed by unaltered HOMA index and intraperitoneal glucose tolerance test [63]. Interestingly, plasma glucose was not increased, but even decreased, pointing to elevated insulin sensitivity, although the plasma insulin was unaltered.…”
Section: Discussionsupporting
confidence: 71%
“…In the study of Teff [64], consumption of fructose-sweetened beverages resulted in lower 24-h circulating glucose in women, while in several animal studies long-term fructose consumption was shown to increase plasma glucose and insulin concentration, as well as to impair glucose tolerance and insulin sensitivity [51,65]. However, in young male rats exposed to fructose diet immediately after weaning, such effects were not observed [63]. The existence of plausible protective mechanism specific for young females remains to be elucidated, although in young and middle-aged women, higher consumption of sugar-sweetened beverages was reported to be associated with an increased risk of development of type 2 diabetes [66].…”
Section: Discussionmentioning
confidence: 99%
“…Our data are in striking contrast to other studies that show increased adiposity, increased liver weight, and increased hepatic TG levels resulting from fructose intake. In the large majority of cases, these effects can be explained by excess caloric intake, in particular due to supplementation with fructose via the drinking water or the lack of an adequate control group (Koricanac et al, ; Spruss et al, ; Vilà et al, ). Effects of fructose feeding mimic those of high‐fat feeding (Ren et al, ; Song et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the ability of the antioxidant defence system to react efficiently under conditions of disturbed homeostasis is largely dependent on age. We have recently shown that a long‐term moderate fructose‐enriched diet (10% fructose solution) applied immediately after weaning affects insulin sensitivity and induces hypertension, hyperlipidemia and low‐grade inflammation . However, this diet has not induced oxidative stress in the rat liver .…”
Section: Introductionmentioning
confidence: 99%